Pelaksanaan Pembelajaran Qira’ah Al-Kutub di Pondok Pesantren Tarbiyah Islamiyah Malalo Kabupaten Tanah Datar - Sayyidah Rezky Ani; Pendi Hasibuan (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This research aims to determine the implementation of qira'ah al-kutub learning at the Tarbiyah Ismaliyah Malalo Islamic Boarding School. This study used qualitative research methods. The informants in this research were the qira'ah ak-pole teachers as key informants and the supporting informants were class VIII students. The data collection techniques used were observation, interviews and documentation. The data analysis used by the Milles and Uberman model is data reduction, data presentation, and drawing conclusions. The data validity technique uses data triangulation. Based on the results of research conducted at the Malalo Islamic Tarbiyah Islamic boarding school, it can be concluded that in general the implementation of qira'ah al-pole learning at the Malalo Islamic Tarbiyah Islamic Boarding School has run smoothly but there are several steps that have not been implemented. Preliminary activities carried out by the qira'ah al-kutub teacher, in making preparations before learning, the ustadzah does not make lesson plans and syllabus but the ustadzah has a plan that has been thought through carefully before teaching but is not written in written form the ustadzah just remembers it, and then In this preliminary activity, the teacher only says greetings and reads prayers and forgets about giving apperception to students. The core activity carried out by the qira'ah al-kutub teacher goes straight into explaining the material without explaining the learning objectives first. And in this closing activity the teacher carries out in accordance with existing provisions.